Differences of lung function in elderly patients with and without hypertension in RSUP Dr. Sardjito Yogyakarta - Bungsu Wahyu Sutriningsih; Sumardi Sumardi; I Dewa Putu Pramantara (Faculty of Medicine Universitas Gadjah Mada, 2013)
ABSTRACTBackground: In the elderly, there is a decrease in lung vital capacity to 68%. The prevalence of hypertension is at the age above 65 years with 13% of the population. The Incidence of lung function decline in chronic heart failure and hypertension was found mainly in the elderly.Aims: The aim of the study was to know the differences ilung function in elderly patients with and without hypertension.Methods: The Study was cross-sectional, a study in November 2012 until January 2013 of the elderly population over 60 years of research with a sample of 58 people (29 people and 29 groups of hypertensive people without hypertension). Inclusion criteria for the study subjects were elderly patients over 60 years of signing the informed consent, can perform spirometry maneuvers correctly. Data were analyzed by T-test to examine some differences in the mean or median, between the two groups.Results: In this research, there were no signifi cant difference in lung function as measured by FVC and FEV1 in the elderly with hypertension and without hypertension (p = 0.984, 95% CI-0, 13-0,139 for FVC and p = 0.83, 95 IK-0, 14-0,116% for FEV1).Conclusion: There is no signifi cant difference in lung function in the elderly with and without hypertension.Keywords: elderly, hypertension, pulmonary function1Speciality